Ursolic Acid Ameliorates Inflammation in Cerebral Ischemia and Reperfusion Injury Possibly via High Mobility Group Box 1/Toll-Like Receptor 4/NFκB Pathway - Wang, Yanzhe; Li, Lei; Deng, Shumin; Liu, Fang; He, Zhiyi (Frontiers in Neurology, 2018)
Toll-like receptors (TLRs) play key roles in cerebral ischemia and reperfusion injury by inducing the production of inflammatory mediators, such as interleukins (ILs) and tumor necrosis factor-alpha (TNF-α). According to recent studies, ursolic acid (UA) regulates TLR signaling and exhibits notable anti-inflammatory properties. In the present study, we explored the mechanism by which UA regulates inflammation in the rat middle cerebral artery occlusion and reperfusion (MCAO/R) model. The MCAO/R model was induced in male Sprague-Dawley rats (MCAO for 2 h, followed by reperfusion for 48 h). UA was administered intragastrically (i.g.) at 0.5, 24 and 47 h after reperfusion. The direct HMGB1 inhibitor glycyrrhizin (GL), was injected intravenously (i.v.) after 0.5 h of ischemia as a positive control. The degree of brain damage was estimated using the neurological deficit score, infarct volume, histopathological changes and neuronal apoptosis. We assessed IL-1β, TNF-α and IL-6 levels to evaluate post-ischemic inflammation. High mobility group box 1 (HMGB1) and TLR4 expression and phosphorylation of nuclear factor kappa-light-chain-enhancer of activated B cell (NFκB) were also examined to explore the underlying mechanism. UA (10 and 20 mg/kg) treatment significantly decreased the neurological deficit scores, infarct volume, apoptotic cells and IL-1β, TNF-α and IL-6 concentrations. The infarct area ratio was reduced by (33.07 ± 1.74) %, (27.05 ± 1.13) %, (27.49 ± 1.87) % and (39.74 ± 2.14) % in the 10 and 20 mg/kg UA, GL and control groups, respectively. Furthermore, UA (10 and 20 mg/kg) treatment significantly decreased HMGB1 release and the TLR4 level and inactivated NFκB signaling. Thus, the effects of intragastric administration of 20 mg/kg of UA and 10 mg/kg of GL were similar. We provide novel evidence that UA reduces inflammatory cytokine production to protect the brain from cerebral ischemia and reperfusion injury possibly through the HMGB1/TLR4/NFκB signaling pathway.